Authorship Methodology in the Biography of the Prophet The Pioneers Stage - Wkkaf, Husen; Naser, Manal (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The prophet’s bibliography is considered as one of the oldest Islamic literature works. These works are historically significant for two reasons. On the first hand, they are seen as manuscripts documenting the life of the Holy Prophet Muhammad (peace is upon him). On the other hand, they predict for the Arab thought methodology in the outsets of entering the field of writing and methodological authorship. This research focuses on the concepts of the prophet’s bibliography, the reasons behind writing it, its resources and its harbingers. Moreover, it studies the content of five books exploring the writing methodology in them. These books, which are considered as the first stage of this type of writings, have been chosen in an effort to gain access to the results that show the authorship methodology in the case of the pioneers. In addition, this research highlights their role in establishing for writing in other types.